Bioethical perspectives of neurostimulation. - Borghi, Luca (Medicina e Morale, 2004)
Neurostimulation and neuromodulation, through subcortical implantation of electrodes, appears to be converting itself in one the most promising branches of neurosurgery. A great number of new therapeutic indications are joining the traditional ones related to Parkinson's disease and other movement disorders: from impaired consciousness to pain-therapy, from epilepsy to neuropsychiatric pathologies. A comparison between these new techniques and the problematic experience of "classical" psychosurgery shows at least one positive and momentous difference, i.e. the reversibility of Deep Brain Stimulation effects. But artificial "modulation" of the nervous system means in one sense "modulation" of the human mind: not only a treatment, but in some way a test of its limits, a development, a transformation. Such a manipulating power applied to the distinctive nucleus of the human person needs a very careful ethical consideration not only of the existing applications of this technology, but also of its future potentialities. So far, only sporadic, though interesting, ethical reflections have been dedicated to this issue, mainly from the very neuroscientists engaged in the challenge. This article tries to offer the necessary elements to start a deep bioethical reflection on the subject, which in view of the mentioned reasons seems to be rather pressing.